2021
DOI: 10.2147/vhrm.s294121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Altitude on Cardiovascular Health: Current Perspectives

Abstract: Globally, about 400 million people reside at terrestrial altitudes above 1500 m, and more than 100 million lowlanders visit mountainous areas above 2500 m annually. The interactions between the low barometric pressure and partial pressure of O 2 , climate, individual genetic, lifestyle and socio-economic factors, as well as adaptation and acclimatization processes at high elevations are extremely complex. It is challenging to decipher the effects of these myriad factors on the cardiovascular health in high alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 199 publications
(222 reference statements)
0
45
0
Order By: Relevance
“…In contrast, maximal HR and SV are lowered and thus maximal Q declines in hypoxic conditions [21]. During submaximal exercise, at a given exercise intensity (at the same absolute workload), HR is greater and SV is lower in hypoxia compared to normoxia [19,20,22]. For example, Clark et al [23] found that submaximal HR during 50-250 W workloads was significantly elevated by a mean of 5-21 bpm at both 2200 m and 3200 m compared to sea level.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, maximal HR and SV are lowered and thus maximal Q declines in hypoxic conditions [21]. During submaximal exercise, at a given exercise intensity (at the same absolute workload), HR is greater and SV is lower in hypoxia compared to normoxia [19,20,22]. For example, Clark et al [23] found that submaximal HR during 50-250 W workloads was significantly elevated by a mean of 5-21 bpm at both 2200 m and 3200 m compared to sea level.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be attributed to the fact that people residing in high-altitude regions develop protective mechanisms against hypobaric hypoxia from birth and have a lower tendency of developing hypertension and having conventional blood pressure measurements that may underestimate the prevalence of hypertension in this population [ 12 , 45 ]. In addition, this population experiences low levels of urbanization, low income, and healthier lifestyles (more physical activity and lower fat consumption) compared to people living in low-altitude regions [ 46 , 47 , 48 ], thereby producing a lower prevalence of coronary risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have further found that the mitochondria respiratory chain is one of the main intracellular sources of reactive oxygen species (e.g., hydrogen peroxide [H 2 O 2 ]) in human cells, which are generated in response to the incomplete electron reduction of molecular oxygen ( Murphy, 2009 ; Bae et al, 2011 ). Reactive oxygen species disrupt the link between Nrf2 and its repressor Kelch-like ECH-associated protein 1, thus releasing Nrf2 to enter the nucleus, where it triggers intracellular redox signalling cascades, which activate, among others, antioxidant and anti-inflammatory genes ( Sazontova et al, 2012 ; Burtscher et al, 2021 ; Mallet et al, 2021 ). Although the exact molecular mechanisms triggered by IHHE are not fully understood, reactive oxygen species-induced signalling pathways are thought to be enhanced when hypoxia and hyperoxia alternate in place of normoxia ( Sazontova et al, 2012 ; Burtscher et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%